Psychometric properties of the High Five Inventory in university students in Ecuador - Quito-Calle, Jessica V.; Cosentino, Alejandro César; González-González, Dalila M.; Guerrero-Vásquez, Luis F. (Frontiers in Psychology, 2025)
IntroductionThe High Five Inventory (HFI) was developed to assess five positive personality traits: erudition, peace, joviality, honesty, and tenacity. Research on positive personality dimensions remains limited, emphasizing the importance of validating assessment tools in different cultural contexts. This study aimed to analyze the psychometric properties of the High Five Inventory (HFI) in a sample of Ecuadorian university students.MethodsAn instrumental study was conducted to evaluate the construct validity and reliability of the HFI. A confirmatory factor analysis (CFA) was performed to assess the inventory's factorial structure. The sample consisted of 1,007 students (403 women, 39.9%) from various faculties at Salesiana Polytechnic University in Ecuador. Prior to data collection, a linguistic review was carried out by a panel of experts, including faculty members, researchers, and students, to ensure clarity and comprehension of the items. The final version of the inventory was administered after obtaining informed consent.ResultsThe CFA results indicated an adequate model fit: χ2 (220) = 859.969, p < 0.001, robust CFI = 0.989, RMSEA = 0.054 (90% CI: 0.050–0.058), and SRMR = 0.045. Additionally, internal consistency was confirmed with Cronbach's Alpha (α) and McDonald's Omega (ω) coefficients ≥ 0.80, demonstrating strong reliability.DiscussionThe findings confirm that the High Five Inventory–Ecuador (HFI-E) exhibits robust psychometric properties, supporting its use in assessing positive personality traits within the Ecuadorian population. The study highlights the relevance of validating personality assessments across different cultural contexts and underscores the potential applications of the HFI-E in psychological and educational settings.